Potential of novel tools for the biorational control of Euschistus heros - Bernal Zuluaga, Jeny Tatiana (2023)
Brazil is the largest producer of soybeans in the world. This recognition has been achieved through years of research, manipulation, and selection of soybean varieties to be productive in tropical climates. Soybean cultivation is of great global importance, primarily for animal feed and oil production. However, soybeans (Glycine max) face limiting factors such as climate, weeds, and pests.one of the most representative pests of soybean crops is Euschistus heros, commonly known as the "brown soybean stink bug". This sucking insect attacks pods and seeds, directly affecting production. The main control method for sucking insects in soybean cultivation is the use of neonicotinoid insecticides, which are compounds derived from nicotine. These compounds act on the nervous system of insects, binding to nicotinic acetylcholine receptors. Their effects cause the death of the insect within hours. However, prolonged, and excessive use of the same control method has selected populations of resistant insects, making control difficult. Additionally, the use of chemical insecticides has negative effects on natural and agricultural ecosystems and impacts human health. Therefore, it is important to research alternative control methods that enrich integrated pest management (IPM) programs and diversify agricultural systems. During this study, a prospecting of new synthetic molecules and essential oils were conducted, focusing on the biorational control of Euschistus heros and selectivity to pollinators and natural enemies. The toxicity of essential oils from Ruta graveolens (rue), Schinus terebinthifolius (red pepper), Cymbopogon citratus (lemon grass), and Morinda citrifolia (noni) was evaluated in concentrations of 25.13 nL/cm 2, 50.26 nL/cm2 and 100.52 nL/cm 2 on third instar nymphs of E. heros. Essential oils of rue, lemon grass and noni showed significant toxicity with a mortality rate ranging from 90% to 100% after 24 hours of exposure. The essential oil of Morinda citrifolia had a LC50 of 11.06 (9.05 - 13.07) nL/cm 2. The synthetic molecules evaluated belong to the group of tetronamides of mucochloric acid. For this study we call them: BEN, M-AN, 3F, DICL, AN, TO2, 4Cl, 2Cl, 2F, 3F, and 4Br. The DICL molecule was the only one that caused significant mortality in E. heros. A dose-response curve was obtained for this molecule, revealing a LC50 of 0.019 (0.017 - 0.020) nL/cm2. Toxicity bioassays were also conducted on pollinators and natural enemies. From the bioassays on pollinators, no significant effect was found on the consumption of DICL-contaminated diet. In the bioassays with the predator, no significant mortality or negative effects on predatory capacity were observed. Our results suggest the potential use of the studied essential oils as insecticidal tools or as a basis to produce new insecticidal products. Additionally, our findings demonstrate the potential use of the DICL molecule as a biorational insecticide, with high efficiency in the control of E. heros and minimal to no effect on the pollinators Apis mellifera and Partamona helleri, as well as the predatory insect Coleomegilla maculata. Future studies could evaluate the selectivity potential of the parasitoid Telenomus podisi. A biological controller that is currently beingused in some soybean fields in Brazil. Keywords: Agricultural entomology. Biorational pest management. Insecticide selectivity.